Monetary Policy Schocks and Economic Growth in Nigeria - Toriola, Anu K.; Adeniwura, Oluwatoba O.; Lawale, Francis Olawale; Eyeke, Anayo V.; Nwakpa, Friday C.; Adeniran, Isaac (Indonesian Journal of Contemporary Education, 2022)
This study examines monetary policy shocks and economic growth in Nigeria. This study following ex post facto research design employed a regression model where economic growth was the dependent variable while money supply, inflation and interest rate were the explanatory variables. Time series data over the period of 1986 to 2018 sourced from Central Bank of Nigeria (CBN) Statistical Bulletin and World Bank Development Index (WDI) was utilized. The study employed the Vector Autoregression (VAR) techniques in the analysis. The result of the vector autoregression estimation shows that money supply exert a significant positive effect on economic growth in Nigeria while inflation and interest rate exert an insignificant positive effect on economic growth in Nigeria. The result proves that monetary policy shocks exert a significant effect on economic growth in Nigeria while interest rate and inflation do not show any effect. It was recommended that the CBN should ensure the downward review of the Monetary Policy Rate of 12% to 9 percent so as to enhance more financial accessibility.